Abiotic and biotic degradation of post‐consumer polypropylene/ethylene vinyl acetate: Wood flour composites exposed to natural weathering. Issue 3 (27th May 2015) - Catto, André L.; Montagna, Larissa S.; Santana, Ruth M.C.
Abstract : The effects of natural weathering on the visual appearance and chemical changes of wood plastic composite (WPC) formulations based on post‐consumer polypropylene/ethylene vinyl acetate (PP‐EVA) matrix were investigated. The WPC composition used was 70/30 (w/w) (recycled PP‐EVA/wood flour). Besides, the effectiveness of using coupling agent on adhesion of WPC and its influence in degradation were evaluated. Colorimetry, scanning electron microscopy, Fourier transform infrared spectroscopy, mechanical test, and biodegradation in simulated soil after natural weathering were used in this research. The results showed the samples with longer exposure time to natural weathering presented significant color change, increased in carbonyl index, and wood loss on weathered WPC surfaces. Weathered WPC exhibited decreased in mechanical properties, higher mass loss after biodegradation test when compared with no weathering WPC, reaching to 15.0% mass loss against 3.7%, respectively. Climatic conditions directly affect the characteristics of all composites, thus indicating a significant photo‐oxidation of the samples with a longer time of exposure to weathering, and this natural ageing has facilitated the WPC biodegradation . POLYM. COMPOS., 38:571–582, 2017. © 2015 Society of Plastics Engineers